Work Life Balance of Women Entrepreneurs - A Literature Survey - Channa, DK (International Journal of Computer Sciences and Engineering, 2025)
Literature Survey Work life balance in entrepreneurship is a very popular amongst the researchers in almost everywhere in the world. Over the years many studies have been done and many articles were published covering various issues and aspects of Women Entrepreneurship. Studies show that there are a lot of trait that work as a push or pull factor for women to become entrepreneurs. This study discusses several aspects of work life balance in women entrepreneurs based on the findings of some already published articles on this matter on certain selected aspects. An attempt has been made to understand and identify the factors which may influence various aspects of affecting entrepreneurial skills of women. At the beginning of this research paper, the meaning of the analyzed in light of several research works. In the next section literature review is done on the factors that are important for creating the balance between the personal and professional life of women entrepreneurs. Besides, this paper also entails the summary and analysis of the findings of all these literatures followed by some new avenues for further research on such issues.